Teacher Strategies for Creating Fun Learning in Elementary Schools - Putri, Rini Syahdiana (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research aims to describe teachers' strategies for creating fun learning in elementary schools. This research uses a qualitative approach with a critical research type. The data source in this research is the VA class teacher at State Elementary School 55/I Sridadi. Research data was obtained using observation, interview and documentation techniques. The data obtained was analyzed by reducing the data, presenting the data, verifying the data and interpreting the data. The results of research regarding teachers' strategies for creating fun learning in elementary schools can be concluded that the methods used by teachers in creating fun learning in elementary schools include firstly greeting students in a friendly and enthusiastic manner, namely by asking about students' news or health, taking attendance at students, giving directions. to always maintain health, and keep up the news. Second, create a relaxed atmosphere by changing seating positions, turning on and listening to music in a low voice while doing tasks. Third, motivating students is by providing encouragement in the form of applause, giving rewards in the form of points, snacks or other snacks. Fourth, use ice breaking, namely by inviting students to clap or sing chants at the beginning, middle or end of learning. Fifth, they use varied learning methods, namely the teacher uses lecture methods, games (learning while playing), group discussions. Apart from that, teachers also use various interesting learning media such as toy animals, objects around the class, cellphones or objects in the natural surroundings.